Philosophy of language and other matters in the work of Anton Marty : analysis and translations - Rollinger, R. D. (Studien zur Österreichischen Philosophie, 2010)
One of the most important students of Franz Brentano was Anton Marty, who made it his task to develop a philosophy of language on the basis of Brentano's analysis of mind. It is most unfortunate that Marty does not receive the attention he deserves, primarily due to his detailed and distracting polemics. In the analysis presented here his philosophy of language and other aspects of his thought, such as his ontology (which ultimately diverges from Brentano's), are examined first and foremost in their positive rather than critical character. The analysis is moreover supplemented by translations of four important works by Marty, including his entire work On the Origin of Language . These are in fact the first English translations of any substantial writings by him. The resulting picture that emerges from the analysis and translations is that Marty has much to say that proves to be of enduring interest for the philosophy of language on a range of topics, especially the meanings of statements, of emotive expressions, and of names as regards both their communicative and their ontological aspects. The volume will be of interest not only to philosophers and historians of philosophy, but also to historians of linguistics and psychology.